Предмет: Алгебра,
автор: RinaShi
Разложить на множители: x^6-x^4-x^2+1
Ответы
Автор ответа:
2
x⁶-x⁴-x²+1=x⁴(x²-1)-(x²-1)=(x⁴-1)(x²-1)=(x²-1)(x²+1)(x-1)(x+1)=(x²+1)(x-1)²(x+1)²
Автор ответа:
1
x^4*(x^2-1)-(x^2-1)
x^4*(x-1)*(x+1)-(x-1)*(x+1)
(x-1)*(x+1)*(x^4-1)
(x-1)*(x+1)*(x^2-1)*(x^2+1)
(x-1)*(x+1)*(x-1)*(x+1)*(x^2+1)
(x-1)^2*(x+1)^2*(x^2+1)
Похожие вопросы
Предмет: История,
автор: maks228arab2221
Предмет: География,
автор: Kate35279
Предмет: Русский язык,
автор: sultanovasaara790
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: 08Кристя80